Driving political issues with political brand storytelling on social media: an online brand persona perspective - Helena van Wyk; Charmaine Du Plessis (Communicare)
Numerous South African political parties have a social media presence to create more awareness around the political issues which they stand for, and thus to attract more voters. Nowadays political parties act as political brands and adopt brand strategies to gain a competitive advantage over opposition parties. This article proposes adopting a social identity theory as a novel approach to how political brands could drive political issues on social media. It is further suggested that due to the complexity of the South African political scene, more attention could be paid to how political brands could leverage political brand stories in conjunction with an online political brand persona on social media to position themselves in a chaotic online political space. To test this, semi-structured expert interviews were conducted with communication professionals in South African public relations agencies who were responsible for creating content for political parties’ Facebook and Twitter accounts. Four themes that became evident in the data collectively indicate that political brands will successfully drive political issues on social media only when they are able to connect emotionally with the political consumer. In this regard, an online political brand persona may be critical in not only eliciting an emotional reaction from political consumers, but also establishing a long-term connection with them based on how credible the political brand is in terms of what they care about and their ability to solve issues.